When Politics Trumps Economics: Contrasting High-Skilled Immigration Policymaking in Germany and Austria. Issue 1 (March 2021) - Kolbe, Melanie
High-skilled immigration (HSI) policy has become of increasing interest among immigrant destination countries, but success in establishing liberal policies has varied considerably across countries. Focusing on two reluctant immigration states, Germany and Austria, this article explains why HSI policy reforms in these two countries have led to starkly diverging outcomes. Whereas previous studies have concentrated on the politics of organized labor market actors and the market-institutional context in which they are embedded, this article contends that variation in HSI policy liberalization also reflects increasing politicization through issue linkage to adjacent immigration domains, in this case, immigrant integration policy. The findings challenge the predominant interest-group–centric work on HSI and show how arguments for and against liberalization can traverse immigration policy domains.